Simulation and experiment of leakage and diffusion of natural gas pipelines with different burial depths under different pressures - Chengbin Zhang; Yaoqiang Hu; Zhao Dong; Zhaofeng Yang; Dongrui Yi (Scientific Reports)
Abstract In this paper, we studied the diffusion characteristics and distribution patterns of gas leakage in soil from buried natural gas pipelines. The three-dimensional simulation model of buried natural gas pipeline leakage was established using Fluent software. Monitoring points of gas leakage mole fraction were set up at different locations, and the influence of buried depth and pressure factors on the mole fraction and diffusion of leaked gas was analyzed. Additionally, a leakage pressure drop test of the buried natural gas pipeline was carried out. The results show that the CH4 gas mole fraction curve at 0.03 m and 0.05 m below the leakage point fluctuates sharply during the second to third second of leakage, with the CH4 gas mole fraction fluctuating by about 7%. The buried depth has the greatest influence on CH4 in the leakage point range of 0.05 m, with the CH4 gas mole fraction above and below the leakage hole differing by nearly 10 times in numerical value. As the buried pipeline depth increases, the pressure drop of the monitoring points at 0.1 m, 0.2 m, 0.3 m, 0.4 m, and 0.5 m is 27.64%, 24.02%, 21.52%, 17.65%, and 17.11%, respectively. In the x-axis direction, CH4 gas presents a U-shaped diffusion in the soil, and after leaking for 200 s, CH4 gas diffused to the top of the pipeline. The errors of the finite element numerical solution and the experimental values of the leakage pressure drop curve of the buried natural gas pipeline under four working conditions are 5.9%, 5.5%, 5.2%, and 5.0%, which are all within the allowable range. The accuracy of the finite element calculation results and the reliability of the test are verified.